What time is it, Mr. Crocodile? - Sierra, Judy; Cushman, Doug (New York : Scholastic, 2004)
Mr. Crocodile's plans to catch and eat some pesky monkeys do not work out and he becomes friends with them instead.
H
490
H
Keywords: Crocodiles -- Fiction; Monkeys -- Fiction; Stories in rhyme